The genetic basis of colorectal cancer in a population-based incident cohort with a high rate of familial disease. Issue 10 (3rd August 2010) - Woods, M O; Younghusband, H B; Parfrey, P S; Gallinger, S; McLaughlin, J; Dicks, E; Stuckless, S; Pollett, A; Bapat, B; Mrkonjic, M; de la Chapelle, A; Clendenning, M; et al.
Abstract : Background and aims: Colorectal cancer (CRC) is the second most frequent cancer in developed countries. Newfoundland has the highest incidence of CRC in Canada and the highest rate of familial CRC yet reported in the world. To determine the impact of mutations in known CRC susceptibility genes and the contribution of the known pathways to the development of hereditary CRC, an incident cohort of 750 patients with CRC (708 different families) from the Newfoundland population was studied. Methods: Microsatellite instability (MSI) testing was performed on tumours, together with immunohistochemistry analysis for mismatch repair (MMR) genes. Where indicated, DNA sequencing and multiplex ligation-dependent probe amplifications of MMR genes and APC was undertaken. DNA from all patients was screened for MUTYH mutations. The presence of the BRAF variant, p.V600E, and of MLH1 promoter methylation was also tested in tumours. Results: 4.6% of patients fulfilled the Amsterdam criteria (AC), and an additional 44.6% fulfilled the revised Bethesda criteria. MSI-high (MSI-H) was observed in 10.7% (n=78) of 732 tumours. In 3.6% (n=27) of patients, CRC was attributed to 12 different inherited mutations in six known CRC-related genes associated with chromosomal instability or MSI pathways. Seven patients (0.9%) carried a mutation in APC or biallelic mutations in MUTYH . Of 20 patients (2.7%) with mutations in MMR genes, 14 (70%) had one of two MSH2 founder mutations. 17 of 28 (61%) AC families did not have a genetic cause identified, of which 15 kindreds fulfilled the criteria for familial CRC type X (FCCTX). Conclusions: Founder mutations accounted for only 2.1% of cases and this was insufficient to explain the high rate of familial CRC. Many of the families classified as FCCTX may have highly penetrant mutations segregating in a Mendelian-like manner. These families will be important for identifying additional CRC susceptibility loci.